Scaling Digital Fisheries Management: The Role of e-PIT in Enhancing Data Accuracy and Operational Efficiency - Agus Suherman; Hamdan Nurul Huda; Raja Rajendra Timilsina; Yayan Hernuryadin; Firli Untoro; R. Tono Amboro; Fatou Sock; Pankaj Koirala (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract